Republic of Congo : First Review Under the Poverty Reduction and Growth Facility Arrangement, and Requests for Waiver of Performance Criteria and Modification of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report for the First Review Under the Poverty Reduction and Growth Facility on the Republic of Congo highlights economic development and fiscal policy. Reflecting the rise in oil prices, the fiscal and current account balance position improved significantly. Congo's medium-term prospects have improved significantly because of the rise in oil prices, notwithstanding the downward revision of oil production. In the banking sector, the government's key objectives are to promote greater market discipline and improve the governance framework as regards bank loans. Although Congo's recent progress provides a good basis for continued program implementation, important risks remain.